(untitled) (Rabi Sangyan, 2024)
This perspective examines the perceptions and interactions of college students with the emerging field of Artificial Intelligence (AI) in their academic environment. The study aimed to explore the interplay between exposure to AI, trust in AI technology, awareness and knowledge of AI, behavioral intentions, and personal experiences, and how these factors collectively influence students’ attitudes and preparedness to integrate AI into their academic pursuits. A considerable portion held post-graduate qualifications, indicating a higher educational background that likely tthat students exhibited a commendable level of proficiency in AI-related concepts and expressed moderate trust in AI technology, crucial for their readiness to adopt AI in educational contexts. Moreover, students demonstrated solid awareness and knowledge of AI, recognizing its potential applications and benefits in various industries, including education. They expressed a proactive willingness to engage in AI-related workshops and activities, indicating strong motivation to incorporate AI into their learning experiences. In conclusion, this study provides valuable insights into the attitudes and preparedness of college students toward embracing AI. The findings have significant implications for educational institutions and policymakers seeking to integrate AI technologies into curricula.